2020
DOI: 10.1002/jsfa.10698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fibers with different physicochemical properties on fermentation kinetics and microbial composition by fecal inoculum from lactating sows in vitro

Abstract: BACKGROUNDEfficient utilization of dietary fibers (DFs) is important for optimizing feed resource utilization and animal health. The aim of the current study was to assess the effects of DFs with varying physicochemical properties (bulky, viscous, and fermentable) on fermentation kinetics and microbial composition during in vitro fermentation by fecal inoculum from lactating sow. According to the physicochemical properties, three different DFs, lignocellulose (LC), modified cassava starch (MCS) and konjac flou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…The low abundance of Anaerovibrio, but the high abundance of Provetella_9, might contribute to the mass production of lactate and acetate during β -glucan and arabinoxylan fermentation. The enrichment of Anaerovibrio followed by the decreased proportion of lactate and acetate was also found in in vitro fermentation trials [ 40 , 41 ]. Another ability of Anaerovibrio was to ferment glycerol into propionate and succinate, among which was propionate produced by the dicarboxylic acid pathway [ 42 ].…”
Section: Discussionmentioning
confidence: 95%
“…The low abundance of Anaerovibrio, but the high abundance of Provetella_9, might contribute to the mass production of lactate and acetate during β -glucan and arabinoxylan fermentation. The enrichment of Anaerovibrio followed by the decreased proportion of lactate and acetate was also found in in vitro fermentation trials [ 40 , 41 ]. Another ability of Anaerovibrio was to ferment glycerol into propionate and succinate, among which was propionate produced by the dicarboxylic acid pathway [ 42 ].…”
Section: Discussionmentioning
confidence: 95%
“…Prevotella has an increased prevalence in subjects with plant-rich diets and produces SCFAs [55,56]. Likewise, Alloprevotella and Anaerovibrio produce SCFAs [57][58][59]. However, elevated abundance of Prevotella are associated with inflammation, hypertension, insulin resistance, and liver disease [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in pigs and humans have found positive effects of dietary fibers on the relief of constipation, which was accompanied by changes in the microbiome [14,15]. Different sources of fiber have different physicochemical properties [16] and differences in the physical and fermentative characteristics of fibers influence their potential to regulate the intestinal microbiome [17][18][19]. It is, therefore, important to study the effects of fiber sources with different properties on constipation and their microbial-regulating function.…”
Section: Introductionmentioning
confidence: 99%
“…Three different sources of fibers were screened in our laboratory: konjaku flour (KON), mainly consisting of glucomannan, which is polymerized by the β-1,4 glycosidic bond, and resistant starch (PRS), which mainly consists of type 3 resistant starch, obtained by gelatinization followed by recrystallization of amylose and amylopectin [20][21][22]. Lignocellulose (LIG) mainly consists of cellulose, which can be slowly fermented in the hindgut, but it can still promote the abundance of some beneficial microbes [18,23]. PRS showed higher concentrations of formic acid and lactate than LIG and KON, whereas KON showed higher concentrations of propionate and butyrate than LIG and PRS in in vitro fermentation experiments [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation